Investigation of stainless steel tubular columns - Liu, Yahua. (2008)
An experimental and numerical investigation into the column strengths of coldformed stainless steel square hollow sections (SHS) and rectangular hollow sections (RHS) is presented in this thesis.The main purpose of the experimental investigation is to provide test data for fixed-ended cold-formed stainless steel square and rectangular tubular compression members. Hence, the test data can be used in the international design specifications for cold-formed stainless steel structures.